Novel nanocomposite forward osmosis membranes for treating highly saline and oily wastewater with low fouling, high water flux and high selectivity - Qin, Detao (2016)
This study focuses on the design and synthesis of a new nanocomposite forward osmosis (FO) membrane that is able to separate highly saline and oily wastewater with low fouling, high water flux and high selectivity, in order to battle against global freshwater scarcity. A new design rationale of FO membrane is developed, which highlights that a genuine FO membrane must possess high antifouling capability as the requisite besides high water flux and high selectivity. Guided by this rationale, as-designed new nanocomposite FO membrane consists of a novel antifouling selective layer on top of a three-dimensionally (3D) interconnected porous support layer. Particularly, graphene oxide (GO) nanosheets assisted phase inversion technology is developed to fabricate the 3D interconnected porous support layer, on top of which dip-coating technique is employed to further construct the hydrogel selective layer in ultrathin thickness (~100 nm).